2
$\begingroup$

I studied differential equations back in the day but we never covered second-order nonlinear equations (that I can recall). I have the following equation:

$$y''=2\biggl(\frac{y'^{2}}{y}-\frac{y'}{x}\biggr)$$

I tried to follow this

Solving a second-order nonlinear ordinary differential equation

but the "2" out front is throwing me off.

I am not a student and this is not homework.

I am fairly certain that the first-order solution to this problem will be a Bernoulli type nonlinear equation and that much I can solve. It's just this 2 out front - and getting from a second-order form to a first-order form - that are throwing me.

Any help in solving for $y'$ would be greatly appreciated!

P. S. This is my first post. My apologies if there are any rules that I have failed to follow.

--

Edit: The form of the first-order solution should have the form

$$y'(x)=P(x)y(x)+Q(x)y(x)^{2}$$

which would then be solved by the Bernoulli method. But how do we get from the second-order form to this one? I've been trying it on my own and nothing is working.

Thanks. Sorry for not being more specific.

$\endgroup$
  • $\begingroup$ Start as in previous question so after first integration you have $y'=A\frac{y^2}{x^2}$ $\endgroup$ – user121049 Oct 17 '17 at 12:54
2
$\begingroup$

$$y''=2\biggl(\frac{y'^{2}}{y}-\frac{y'}{x}\biggr)$$ Factor out $y'$. Notice that $y'=0$ is one of the solutions. Anothere we can find from: $$ \frac{y''}{y'}=2\frac{y'}{y}-2\frac{1}{x} $$ It can be rewritten as follows (use properties of logarithm): $$ (\ln y')'=2(\ln y)'-2(\ln x)'\\ (\ln y')'=\left(\ln \left(\frac{y}{x}\right)^2\right)' $$ Integrate: $$ \ln y'=\ln\left(\frac{y}{x}\right)^2+C $$ Exponentiate (and then you receive the equation specified in comments): $$ y'=e^C \left(\frac{y}{x}\right)^2=A \left(\frac{y}{x}\right)^2 $$

$\endgroup$
  • $\begingroup$ Kostiantyn Lapchevskyi That isn't quite right. I followed what you did (I think) this isn't the form I think we should have. Sorry, I should have been more clear in the original post. I will edit it. $\endgroup$ – user492494 Oct 17 '17 at 15:10
  • 1
    $\begingroup$ $P(x)=0$, $Q(x)=A/x^2$ $\endgroup$ – user121049 Oct 17 '17 at 15:17
0
$\begingroup$

For this equation, define $y=\frac x z$ making the equation to be $$\frac {x z''}{z^2}=0\implies z''=0\implies z'=c_1\implies z=c_1x+c_2\implies y=\frac x{c_1x+c_2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.